Analysis of Fixed Asset Listing in the Legal Section of the Medan City Secretary at the Medan Mayor's Office - Sherlita Mardiani; Rahmat Daim Harahap (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
The purpose of this research is to find out how the recording of fixed assets in the Legal Section of the Medan City Secretary at the Medan Mayor's Office. This study researched and collected data using descriptive qualitative methods in the form of direct data that was processed in the form of tables and additional data through books, the internet and related articles. The results of this study indicate that the Medan Mayor's Office, including the Medan Regional Secretary's Legal Section, has been truly optimal in managing fixed assets from the submission of the Medan City Regional Secretary General Section in the past year.